2019
DOI: 10.1039/c9nr01262a
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin of the high-performance light-emitting InGaN/AlGaN quantum disks

Abstract: 3D model showing the boomerang shape of the InGaN/AlGaN quantum disks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
(33 reference statements)
0
9
0
1
Order By: Relevance
“…Due to different chemical potential for different facets, GaN shows growthrate anisotropy. [27,37] A closer examination of the QWs revealed that the growth planes of InGaN/AlGaN evolved from (0112) to (0111) plane within four pairs of QWs from bottom to top. A schematic 3D illustration of the InGaN/AlGaN QWs@GaN NR is shown in Figure 1d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to different chemical potential for different facets, GaN shows growthrate anisotropy. [27,37] A closer examination of the QWs revealed that the growth planes of InGaN/AlGaN evolved from (0112) to (0111) plane within four pairs of QWs from bottom to top. A schematic 3D illustration of the InGaN/AlGaN QWs@GaN NR is shown in Figure 1d.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] Facets with larger slope display decreased quantum-confined Stark effect and thus could exhibit higher light emitting efficiency. [21,26,27] Selected-area molecular-beam epitaxy (MBE) growth has been demonstrated to be a controllable way of growing ternary III-N based nanorods in a bottom-up approach, which could dramatically reduce the number of defects (especially dislocations and/or stacking faults). [26,28,29] The nucleation of the nanowires from adatoms can be limited only to the exposed surface on the substrate leading to uniform morphology of the nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large surface-to-volume ratios of the 1D nanomaterials, the surface plays a key role in the optical properties of 1D nanometer material LEDs [80][81][82][83][84][85][86][87][88][89][90]. Due to the existence of surface states, a Fermi-level pinning effect will occur, and the resulting transverse electric field effect and related surface non-radiative recombination will be very unfavorable to one-dimensional nanostructured-led devices [80][81][82].…”
Section: Core/shell Structure Methodsmentioning
confidence: 99%
“…It can be proved by the experimental results that white LEDs based on dodecagonal ring structures are a platform enabling a high-efficiency warm white light-emitting source. Recently, high-performance InGaN/GaN and InGaN/AlGaN nanowire heterostructure LEDs were prepared by different research groups [88][89][90][91][92][93][94]. A schematic diagram of a nanowire LED with an InGaN/AlGaN core-shell heterostructure is shown in Figure 5.…”
Section: Core/shell Structure Methodsmentioning
confidence: 99%
“…В работе [12] отмечается, что эпитаксия соединений A 3 B 5 может сопровождаться неравновесным упорядочением двух типов (композиционной автомодуляцией и атомным порядком), которое связывается с реконструкцией поверхности. В частности, для соединений AlGaN встречается как композиционная автомодуляция [13], так и атомный порядок [14]. На рис.…”
unclassified